Supplementation strategies for beef heifers in tropical pastures in the preweaning and rearing periods - Maza Ortega, Román Enrique (2018)
This research was conducted from two studies with beef heifers grazing submitted different supplementation strategies and the results are here presented in two manuscripts. In the first manuscript, effects of supplement amounts on productive and nutritional performance and metabolic profile were evaluated in suckling female calves under grazing in the tropics. The treatments were 1) 4 g/kg body weight (BW) of supplement or 2) 6 g/kg BW of supplement. Forage and organic matter (OM) intake did not affect (P>0.12) by amounts of supplement, though crude protein and non-fibrous carbohydrates intake were greater (P<0.04) by increasing supplement amount. There was no effect (P>0.23) the amounts of supplement on OM and CP digestibility. In addition, production of microbial nitrogen was similar (P>0.15) between treatments, however, the excretion of urea nitrogen in the urine increased (P<0.01) by increasing supplement amount. The metabolic profile of the animals was not affected (P>0.99) by amounts of supplement. Mean daily gain, longissimus dorsi area, fat thickness over rump of the animals did not affect (P>0.26) by amounts of supplement. However, there was trend of increasing (P=0.074) in fat thickness over loin by increase the supplement amount. Although the body growth of animals was similar (P>0.18) between treatments, there was observed a trend of increase (P=0.064) in ratio BW:Height at the withers by increasing supplement amount. The results indicate that increasing supplement amounts does not improve the productive and nutritional performance and metabolic status in female calves on creep- feeding system. In the second experiment, effects of supplement amounts pre-weaning and rearing on productive and nutritional performance, metabolic profile, and ovarian activity were evaluated in heifers under grazing in the tropics. Forty Nellore heifers averaging 8.5±0.06 months and 248.6±3.3 kg body weight (BW) were distributed in a completely randomized design in a 2 × 2 factorial scheme with four treatments and ten replicates. The treatments were: 1) 4 g/kg of BW of supplement pre-weaning and rearing; 2) 4g/kg of BW of supplement pre-weaning and 6 g/kg rearing; 3) 6 g/kg of BW pre- weaning and 4 g/kg of BW rearing and; 4) 6 g/kg of BW pre-waning and rearing. Crude protein (CP), organic matter (OM) intake were increased (P≤0.02) by increasing the amounts of supplement in the rearing. Additionally, increasing supplements amounts in the rearing increased the digestibility the OM and CP (P<0.05). Means insulin and glucose concentrations were greater (P<0.03) for heifers that received greater amounts of supplement in the rearing. Daily gain and fat thickness in the rump were increased (P<0.01) by increasing supplement amounts in the rearing. Amounts of supplement did not influence (P>0.15) body growth of heifers. However, follicular number, diameter and progesterone concentration were greater (P<0.02) for heifers that received greater amounts of supplement in the rearing. The results indicate that increasing supplement amounts in the rearing has greater positive impact on performance, metabolic status, and ovarian activity of heifers under grazing than increasing supplement amounts in the pre- weaning.